Synthesis Chemical Reaction Model via P-Fuzzy Systems - Wasques, Vinícius F. [UNESP]; Pedro, Francielle Santo; Esmi, Estevão; Barros, Laécio C. (Springer Nature, 2023)
This paper studies synthesis chemical reactions from the perspective of p-fuzzy systems. A p-fuzzy system consists of approximating the solution of differential equations, without using differential equation solving techniques. To this end, this work considered a qualitative knowledge of a synthesis chemical reaction, and proposed a modeling based on fuzzy rule-based system in order to produce an approximate solution of the problem. An example is provided to illustrate the methodology.
Keywords: Differential equation; Fuzzy rule-based systems; P-fuzzy systems; Synthesis chemical reaction